Predictors of junior versus senior elite performance are opposite: a systematic review and meta-analysis of participation patterns - Barth, M.; Güllich, A.; Macnamara, B. N., Hambrick, D. Z. (Sports Medicine, 2022)
Background: Does early specialization facilitate later athletic excellence, or is early diversification better? This is a longstanding theoretical controversy in sports science and medicine. Evidence from studies investigating athletes` starting age, childhood/adolescent progress, and amounts of coach-led practice and peer-led play in their main sport and in other sports has been mixed. Each participation variable was positively correlated with performance in some studies but uncorrelated or negatively correlated with performance in others. However, samples were heterogeneous in age, sports, and performance levels. Objective: This study aimed to establish robust, generalizable findings through a systematic review and meta-analysis. We investigated three questions: (1) did higher- and lower-performing athletes differ in childhood/adolescent progress, starting age, or amounts of main-sport or other-sports practice or play; (2) do effects differ between junior and adult athletes, compared performance levels, or types of sports; and (3) are effect sizes from different predictors associated with one another? Methods: We conducted a systematic literature search in SPORTDiscus, ERIC, ProQuest, PsycINFO, PubMed, Scopus, WorldCat, and Google Scholar until 28 February 2021. Selection criteria included original research studies comparing higher- versus lower-performing athletes regarding one or more of our predictor variables within defined age categories, sports, and sex, and reporting effect sizes or data needed to compute effects sizes. Mean meta-analytic Cohen`s d was calculated for each predictor. Quality of evidence was evaluated using GRADE. Results: In total, 71 study reports met all eligibility criteria and included 262 international athlete samples, 685 effect sizes, and a total sample size of 9241 athletes from local to Olympic competition level and from diverse sports. The following findings emerged. (1) Compared with their national-class counterparts, adult world-class athletes had more childhood/adolescent multi-sport coach-led practice, a later main-sport start, less main-sport practice, and slower initial progress (|0.23|< d¯<|0.50|; all p < 0.001). (2) The opposite was true for predictors of junior-age performance: higher-performing juniors had an earlier main-sport start, more main-sport practice, less other-sports practice, and faster initial progress (|0.23|< d¯< |0.61|; all p < 0.001). (3) Main-sport or other-sports peer-led play had negligible effects (all p > 0.05). (4) Results were robust across types of sports. (5) Effect sizes from different predictors were associated with one another (|0.64|< r <|0.79|). A GRADE assessment revealed a low quality of evidence for peer-led play but a moderate to high quality of evidence for all other predictors. Discussion: Excess childhood/adolescent specialized practice may hinder athletes` long-term development through overuse injury, burnout, suboptimal athlete-sport match, and limiting long-term learning capital. By contrast, adult world-class athletes` childhood/adolescent multi-sport practice with reduced main-sport practice implied a relatively resource-preserving, cost-reducing, and risk-buffering pattern that yielded greater long-term sustainability and practice efficiency.